The adaptation process and preliminary psychometric evaluation of the Polish version of Kiddo-KINDL questionnaire - Hanć, Tomasz; Ravens-Sieberer, Ulrike (Anthropological Review, 2019)
The assessment of health-related quality of life (HRQoL) is increasingly important in fields of public health, medicine, sociology and psychology. The aim of the study was to evaluate the psychometric properties of the Polish version of generic Kiddo-KINDL questionnaire for adolescents. The psychometric evaluation was performed using 96 questionnaires fulfilled by adolescents aged 12–16 years. Cronbach’s α coefficient for internal consistency and split-half reliability was estimated as well as ceiling, floor effect and correlations among the subscales and total score. The mean reliability for subscales was 0.65 and the Cronbach’s α coefficient for the total score was 0.85. The lowest α coefficient was for the School dimension (0.44) and the highest was achieved for the Self-esteem (0.80). The correlation between two parts of the questionnaire and split-half reliability was 0.66 and 0.80 respectively. The first psychometric evaluation of the Polish Kiddo-KINDL showed promising basic measurement properties, but it needs farther assessment, including convergent, construct and discriminant validity estimation.